The Efforts of Early-Childhood Education Managers in Achieving Accreditation to Improve the Quality of Education Organization - Musa, Safuri; Uthartianty, Rita (Universitas Negeri Semarang, 2019)
The background of this research is that less than 10 per cent of the 846 ECE institutions in West Bandung District have accreditation of institutions, so the implementation quality doesn’t meet the education national standard. Accreditation, although it is an intermediate goal that must be achieved by each institution, has a great influence on the quality of implementation, the quality of graduates and the credibility of the institution. The purpose of the research is to describe the efforts and obstacles of ECE managers in achieving accreditation to improve the quality of education organization according to national education standard. The research uses descriptive qualitative for research method with case study approach in West Bandung District. Research results of the study: (1) the efforts of ECE managers in achieving institution accreditation; joining socialization, learning accreditation documents, consulting with the supervisors, taking discussions and workshops with fellow institutions that will participate in the accreditation, inviting resource persons and arranging infrastructure, and (2) the obstacles faced by managers in achieving accreditation are limited sources and infrastructure, and weak management. The research concludes that ECE management requires a serious effort by mobilizing various available resources to achieve accreditation because the implementation doesn’t pay attention to eight education national standards.